Radiofluorinated N-Octanoyl Dopamine ([18F]F-NOD) as a tool to study tissue distribution and elimination of NOD in vitro and in vivo - Pretze, Marc; Pallavi, Prama; Klotz, Sarah; Binzen, Uta; Greffrath, Wolfgang; Treede, Rolf-Detlef; Yard, Benito A.; Wängler, Carmen; Wängler, Björn (Journal of medicinal chemistry, 2016)
To mitigate pretransplantation injury in organs of potential donors, N-octanoyl dopamine (NOD) treatment might be considered as it does not affect hemodynamic parameters in braindead (BD) donors. To better assess optimal NOD concentrations for donor treatment, we report on the fast and facile radiofluorination of the NOD-derivative [18F]F-NOD [18F]5 for in vivo assessment of NOD’s elimination kinetics by means of PET imaging. [18F]5 was synthesized in reproducibly high radiochemical yields and purity (>98%) as well as high specific activities (>20 GBq/μmol). Stability tests showed no decomposition of [18F]5 over a period of 120 min in rat plasma. In vitro, low cell association was found for [18F]5, indicating no active transport mechanism into cells. In vivo, [18F]5 exhibited a fast blood clearance and a predominant hepatobiliary elimination. As these data suggest that also NOD might be cleared fast, further pharmacokinetic evaluation is warranted.